3-D structure, volume, and DNA content of erythrocyte nuclei of polyploid fish - Bytyutskyy, Dmytro; Kholodnyy, Vitaliy; Flajšhans, Martin (Cell biology international, 2014)
We have explored the potential relationship between ploidy level, DNA content (pg DNA nucleus(-1)), and dimensional characteristics, such as volume (μm(3)), surface area (μm(2)), and 3-D structure of erythrocyte nuclei in a series of fish ploidy level models using Feulgen image analysis densitometry, flow cytometry, and confocal laser scanning microscopy. The species were diploid tench (Tinca tinca) (2n), Cuban gar (Atractosteus tristoechus) (2n), triploid tench (3n), evolutionary tetraploid sterlet (Acipenser ruthenus) (4n), evolutionary octaploid Siberian sturgeon (A. baerii) (8n), triploid Siberian sturgeon exhibiting dodecaploidy (12n), evolutionary 12n shortnose sturgeon (A. brevirostrum), and experimentally obtained sturgeon hybrids that were tetraploid, hexaploid (6n), heptaploid (7n), octaploid, decaploid (10n), dodecaploid and/or tetradecaploid (14n). Increase in ploidy was accompanied by growth of the nucleus and an increase in the number of flattened ellipsoid nuclei with increased transverse diameter. The volume (Vvoxel ) of erythrocyte nuclei, as the sum of voxels calculated from live cells, seems more accurate than volume (Vaxis ) calculated from measuring the major and minor axis, especially at higher and odd ploidy levels. Data of absolute and relative DNA content were in agreement with previously published reports. Species of the same ploidy level, but differing in DNA content, had a similar mean erythrocyte nuclear volume (Vvoxel ), as demonstrated in sterlet and a hybrid of sterlet and beluga (48.3 and 48.9 μm(3), respectively), with a respective mean DNA content of 3.74 and 3.10 pg DNA nucleus(-1). A similar relationship was found for the ploidy 6n, 10n, 12n. The surface-to-volume ratio decreased non-linearly with increasing ploidy. The DNA in erythrocyte nuclei appeared to be more densely packed with increase in ploidy level.
Keywords: ploidy; zobrazování trojrozměrné; Cell Nucleus; sturgeon; DNA content; buněčné jádro; Imaging, Three-Dimensional; erythrocyte; nuclear volume; Cyprinidae; DNA cytometry; Animals; zvířata; erytrocyty; DNA; Erythrocytes; Polyploidy; 3D confocal analysis; polyploidie